Polysomnographic Evaluation of OSA in Patients of Bronchial Asthma - Yousoof, Dar Mohd; Mohammad, Jamal; Shahnawaz, Mir; Nazir, Shah Naveed; Khursheed, Dar; Suriya, Syed (International Journal of Innovative Research in Medical Science, 2020)
Introduction: Bronchial asthma a common non-communicable disease affecting more than 300 million people world-wide. Compared to general population quality of sleep is poor in asthma patients due to various factors like poor control of asthma, co-morbidities like allergic rhinitis and oesophageal reflex disease but little is known about the potential role of obstructive sleep apnoea. Aims and objectives: This study was conducted is to evaluate the association between Asthma and risk of developing Obstructive Sleep Apnoea. Materials and methods: This was a prospective design study conducted on 137 patients of diagnosed bronchial asthma attending out-patient department of a referral chest from north India after ethical clearance. These patients underwent Berlin score assessment first and later level-1 polysomnography to evaluate for OSA. Results: prevalence of PSG documented OSA observed was 53.3% which is significantly higher than the general population and there was significant association with increasing age as 54.7% of patients were in middle aged population (40-60 years) and obesity with 67.1% patients having OSA with BMI >30 compared to 37.5% prevalence only with BMI <30, as well as with severity of asthma. Besides OSA was seen in 91.9% of Berlin high risk group patients, while it was found in only 21.3 % of Berlin low-risk group. Conclusion: prevalence of OSA in asthma patients is significantly higher as compared to general population and there is significant positive co-relation between severity of asthma, BMI, increasing age and higher Berlin score with the overall prevalence of OSA.